2021
DOI: 10.1111/jocn.16031
|View full text |Cite
|
Sign up to set email alerts
|

Spanish nurses’ experiences with personal protective equipment and perceptions of risk of contagion from COVID‐19: A qualitative rapid appraisal

Abstract: Aims and Objetives Explore nurses' experiences and perception of risk regarding the use of personal protective equipment during the first wave of the pandemic in Spain. Background The contribution of our study is to use qualitative methods to understand nurses' experiences and perceptions of the risk of the contagion linked to the shortage of PPE during the first wave of the pandemic, whose explosive start strained health systems around the globe. Design Qualitative descriptive design according to the Rapid Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
12
0
3
Order By: Relevance
“…No se hallaron diferencias entre enfermeras de la costa o la sierra respecto al miedo al contagio. Estos resultados son consistentes con los encontrados por otros investigadores (Meisenhelder & La Charite, 1989;Bennett, 1998;Montes et al,2021;Salvatierra Ávila et al,2021;Valencia González et al, 2021;Romeu et al, 2022).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No se hallaron diferencias entre enfermeras de la costa o la sierra respecto al miedo al contagio. Estos resultados son consistentes con los encontrados por otros investigadores (Meisenhelder & La Charite, 1989;Bennett, 1998;Montes et al,2021;Salvatierra Ávila et al,2021;Valencia González et al, 2021;Romeu et al, 2022).…”
Section: Discussionunclassified
“…(Ávila et al,2021) Esto puede vincularse a nuestros resultados. Las enfermeras que trabajan en equipo durante la crisis sanitaria tienen un nivel de prevalencia de percepción de riesgo muy significativamente más bajo, creemos este resultado también puede explicarse si se tiene en cuenta lo planteado por Romeu et al, (2022), quienes encontraron que la gravedad de la escasez de equipo de protección personal enfermeras y otros profesionales sanitarios afectados durante la primera ola de la pandemia en España, la reutilización de equipos de protección personal se relacionó con la percepción de riesgo entre las enfermeras españolas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Beal et al (2020) state that during the COVID-19 pandemic, healthcare team members had to rely on each other to make the right decisions quickly to save many lives under harsh working conditions. Romeu Labayen et al (2021) found in their study that nurses felt a lack of trust in management when they saw that management was more concerned with allocating equipment rather than their safety.…”
Section: Discussionmentioning
confidence: 99%
“…We read, with great interest, the article by Romeu-Labayen 'Spanish nurses' experiences with personal protective equipment and perceptions of risk of contagion from COVID-19' (Romeu-Labayen et al, 2021). As medical students in the United Kingdom (UK), we would like to share our experiences of personal protective equipment (PPE) shortages and highlight how the issues expressed in the paper were felt beyond the nursing community.…”
Section: Healthcare Students' Experience Of Personal Protective Equip...mentioning
confidence: 99%